Minimum inhibitory concentration of cocoa pod husk extract in Enterococcus faecalis extracellular polymeric substance biofilm thickness - Tamara Yuanita; Latief Mooduto; Reinold Christian Lina; Fajar Agus Muttaqin; Ika Tangdan; Revina Ester Iriani Marpaung; Yulianti Kartini Sunur (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Root canal treatment constitutes a treatment sequence for infected pulp to eliminate the etiological factors of pulp necrosis and periapical lesion. Enterococcus faecalis (E. faecalis) is an organism commonly found in a high proportion of root canal failure because of its ability to form biofilm. Degradation of extracellular polymeric substance (EPS) by oxidizing agents such as sodium hypochlorite is the first step in removing biofilm. However, the toxicity of sodium hypochlorite constitutes the main concern and, therefore, the safest alternative irrigants possible are required. The use of fruits, herbs and plants is widespread, especially in the fields of medicine and dentistry. Food crops are known to be rich in bioactive compounds, especially polyphenols, which have antioxidant and antimicrobial properties. Cocoa pod husk extract can, therefore, represent an alternative irrigant. Purpose: This study aimed to determine the minimum inhibitory concentration of cocoa pod husk extract in relation to the thickness of E. faecalis EPS biofilm. Methods: Four groups of E. faecalis cultured biofilm samples were analysed: group one contained E. faecalis without cocoa pod husk as a positive control; group two contained E. faecalis with 1.56% cocoa pod husk extract; group 3 contained E. faecalis with 3.125% cocoa pod husk extract; and group 4 contained E. faecalis with 6.25% cocoa pod husk extract. The biofilm thickness of all groups was measured by confocal laser scanning microscopy with statistical analysis subsequently undertaken by means of a post hoc test and Tukey HSD. Results: The average values of EPS biofilm thickness were as follows: group 1: 9500 nm; group 2: 8125 nm; group 3: 8000 nm; and group 4: 6375 nm. A post hoc Tukey HSD test indicated a significant difference between group 1 and group 4, while in group 2 and group 3 compared to group 1, there were no significant differences with the values of each being p = 0.340 and p = 0.267 (p>0.05). Conclusion: 6.25% cocoa pod husk extract reduces E. faecalis EPS biofilm thickness.